2019
DOI: 10.1111/josi.12316
|View full text |Cite
|
Sign up to set email alerts
|

Medical Neoliberalism in Rape Crisis Center Counseling: An Interpretative Phenomenological Analysis of Clinicians’ Understandings of Survivor Distress

Abstract: A neoliberal medicalized framework shapes society's understanding of distress as a disease or disorder and places the responsibility on individuals to "fix" themselves, situating the problem within a person, rather than in a sociopolitical context. This framework has become increasingly prevalent in Western society and has permeated rape crisis centers (RCCs), which play a vital role supporting sexual violence survivors. The goal of the present study was to explore the impact of a neoliberal medicalized discou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
0
13
0
2
Order By: Relevance
“…Furthermore, the results appeared to be affected by whether the survivor and the caseworker were ethnically matched, as matched survivors were more likely to utilize services compared to those not matched. A lack of diverse staff was also perceived to be a barrier to serving SA survivors of colour among service providers interviewed in other studies (DeLeon, 2017 ; Peters, 2019 ). In particular, ethnic minority women may be reluctant to seek services from White, middle-class women who may be unable to understand their concerns (Ullman & Townsend, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the results appeared to be affected by whether the survivor and the caseworker were ethnically matched, as matched survivors were more likely to utilize services compared to those not matched. A lack of diverse staff was also perceived to be a barrier to serving SA survivors of colour among service providers interviewed in other studies (DeLeon, 2017 ; Peters, 2019 ). In particular, ethnic minority women may be reluctant to seek services from White, middle-class women who may be unable to understand their concerns (Ullman & Townsend, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…A lack of knowledge about gender and sexual minorities seemingly hampered service delivery in SA clinics in Belgium (Hendriks, Vandenberghe, Peeters, Roelens, & Keygnaert, 2018 ; Vandenberghe et al, 2018 ) and Canada (Du Mont, Kosa, Abavi, Kia, & Macdonald, 2019 ; Du Mont, Kosa, Solomon, & Macdonald, 2019 ). Other studies also suggested that increased cultural sensitivity towards gender and sexual minorities is needed at services (Peters, 2019 ; Ullman & Townsend, 2007 ; White et al, 2019 ). For example, a sizable portion of transgender individuals experience discrimination based on their gender expression or identity at RCCs (Kattari, Walls, & Speer, 2017 ; Kattari, Walls, Whitfield et al, 2017 ; Seelman, 2015 ) and in the CJS (Jordan et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This view is termed by some as 'biopsychiatry', a hegemonic discourse that depicts cognitive, affective and behavioural complications as tantamount to diseased brain states, thus shaping mental health services fundamentally (public and private research, treatment, education, and professional initiatives) (Dougherty, 2019). Peters (2019) for example, in her analysis of clinician FORENSIC TREATMENT OF AGENCY 45 interviews at rape crisis centres, illustrates how distress is operationalised as a disease for which the 'infected' become responsible for their own management. Being a common diagnosis for survivors of sexual violence, post-traumatic stress disorder (PTSD), which has been an official diagnostic category since the 1980s, exemplifies as much, given its characteristic focus on intra-individual phenomena (flashbacks, hypertension).…”
Section: Chapter Five: Psychology and Neoliberalismmentioning
confidence: 99%